Memprediksi Kawasan Rawan Banjir Berdasarkan Luas Daerah Genangan Banjir di Kota Samarinda - Yayuk Sri Sundari (Department of Architecture, Faculty of Engineering, 2018)
ABSTRACTChanges in land use patterns affect the potential decline in the region caused by the increasingly widespread use of land for building. which caused a reduction in water catchment areas occurrence inundation or flooding. The purpose of this study was to predict the flood prone areas in the subzone Karang Mumus. Results are expected to be known biophysical subzone Karang Mumus subzone. Analysis region extensive flooding subzone Karang Mumus of 80.48%, topography of hilly and flat areas in particular there are in the groove river Karang Mumus. Slope is a factor that has a major effect on the level of vulnerability to flooding. Land use affects the determination of the flood prone areas, land use relates to the size of the water runoff. Biophysical conditions in subzone Karang Mumus for the district that are prone to flooding, District of North Samarinda flat slope of 0-8% with an area of 12356.3 hectares of 31.0265%, 25-40% slope class steep slope with a spacious 269.2 hectares area of 0.6760%, slope>40% grade incline is very steep with an area of 12.7 hectares of 0.0319%. For closure / shrub land use 12700.7 hectares of 31.8913%, the mining area of 4.0864% 1627.4 hectares , with an area of 1814.9 hectares settlement amounted 4,557,2%, open land with an area of 781.5 hectares amounting to 1.9623%, with an area of forest land cover 47.1 hectares of 0.1183% and a vast pool of 1,506 hectares of 55.72%.Keywords: slope, flood prone areas, extensive flooding.